Unlocking Male Youth Soccer Players’ Peak Performance Potential: Exploring the Impact of Maturation, Age, and Physical Demands on Neuromuscular Injury Risk and Recovery Following Competitive Matchplay - Imanol Martin-Garetxana; Francisco Ayala; Mark De Ste Croix; Jon Larruskain; Josean Lekue; Jonathan Hughes (Youth)
This study investigated the 7-day recovery period post-soccer matches in elite male academy players. We analyzed changes in physical performance, stretch-shortening cycle capability, landing mechanics, muscle damage, and perceived well-being while also considering the influence of players’ maturity status, chronological age, and physical demands on post-match responses. In a prospective, observational, mixed longitudinal study design, twenty-six players (U14 = 14 [age = 13.9 ± 0.2 y, and U16 = 12 [age = 15.1 ± 0.2 y]) undertook testing at baseline (1 h pre-match), immediately post-match (0 h), and 48-, 72-, 96-, and 120 h post-match for measures in creatine kinase (CK), urea (UR), CMJ height, 20 m sprint time, reactive strength index (RSI), leg stiffness (LS), landing mechanics, and perceived well-being. Players were also tested pre [168-h] and post the subsequent match. Results showed significant alterations 0 h post-match in CK (+71.3%), UR (+12.8%), CMJ height (−5.3%), 20 m sprint time (+3.8%), RSI (−9.6%), LS (−11.5%), and perceived well-being (−7.7%), with landing mechanics being unaffected. All parameters returned to baseline at 48 h, except for CK and UR, which remained elevated until 168 h. The players’ initial scores influenced how they responded after the match during the week. In conclusion, coaches should focus on post-match strategies to enhance muscle recovery, especially for youth players with a lower training status, given the extended recovery period observed for muscle damage markers.